Strategies to optimize the use of organic fertilizers in smallholder coffee plantation. Issue 1 (January 2022) - Wulandari, S; Ferry, Y; Hasibuan, A M
Abstract: The demand for organic coffee is increasing in line with increasing competition and consumer preferences for healthier products. On the other hand, the application of organic fertilizers in smallholder coffee plantations is still low. The research aims to map the constraints of organic fertilizers usage and develop strategies to accelerate organic fertilizers application in smallholder coffee plantations. Data analysis was performed using the scoring method. The results showed that farmers applied more inorganic fertilizers. Constraints of organic fertilizers application are related to technical, economic, and institutional aspects. Strategies to optimize the use of organic fertilizers in smallholder coffee plantations include providing capital and financial support with subsidized interest rates and strengthening farmer institutions as the priority. Other strategies include introducing an integrated coffee livestock system and providing local government incentives for promoting and organic certification assistance. Institutions involved in implementing the strategy include local governments, research institutes, financial institutions, coffee processing industries, exporters, extension officers, certification bodies, farmers' groups, cooperatives, and associations. The strategies are essential to overcome the existing problems and constraints in organic coffee farming development and increase farmers' interest in applying organic fertilizers.